Sustainable Analysis of Calophyllum Inophyllum Oil for Eco-Friendly Green Lubricants as an Alternative to Mineral Oils - Kiki Darmawan; Novan Habiburrohman; Mudrikah Mudrikah; Mohammad Na’im Humam; Bagus Sriwijaya; Luchyto Chandra Permadi; Farisan Robbani; Mojibur Rohman (G-Tech: Jurnal Teknologi Terapan, 2026)
Calophyllum Inophyllum (nyamplung) Oil is recognized as a promising non-edible vegetable oil for the development of sustainable green energy lubricants. This study aims to improve the physicochemical characteristics of nyamplung oil through a two-step transesterification followed by esterification using trimethylolpropane (TMP), and to assess its tribological performance. The refined oil exhibited a flash point of 212 °C (ASTM D92) and a pour point of 8 °C (ASTM D97), indicating excellent thermal and flow stability. The kinematic viscosity was 38.3 cSt (ASTM D445) and the density 0.88 g/cm³ (ASTM D4052), both within industrial lubricant standards. The acid value decreased markedly from 36.5 to 1.62 mg KOH/g, while the iodine value (0.006 g I₂/100 g) and peroxide value (0.23 Meq/kg) demonstrated chemical stability. FTIR analysis confirmed the formation of ester functional groups, and GC–MS results showed a balanced distribution of saturated and unsaturated fatty acids. Overall, the modified Calophyllum Inophyllum Oil fulfills key technical criteria for eco-friendly green energy lubricants and shows strong potential as a renewable alternative to conventional mineral-based lubricants in industrial applications. Nevertheless, its crude form presents several drawbacks, including high acid and peroxide values as well as poor oxidative stability.